The Influence of Leadership and Motivation on Employee Performance (Literature Review MSDM) - Riza Akbar, Kurnia (Dinasti International Journal of Digital Business Management, 2025)
The aim of this research is to develop hypotheses regarding the influence between variables that will be used in future research within the scope of human resource management studies. The writing method used in this research is library research, sourced from previous studies. Online media platforms such as Google Scholar, Publish or Perish, and other academic online media were utilized to obtain previous studies. The results of this research are as follows:1. Leadership influences employee performance; 2. Work motivation influences employee performance.